Assessment of retinal pigment epithelium tears in eyes with submacular hemorrhage secondary to age-related macular degeneration - Tomoko Ueda-Consolvo; Syogo Takahashi; Toshihiko Oiwake; Tomoko Nakamura; Masaaki Ishida; Shuichiro Yanagisawa; Atsushi Hayashi (Scientific Reports)
Abstract To assess retinal pigment epithelium (RPE) tears in eyes which underwent pars plana vitrectomy (PPV) for submacular hemorrhage (SMH) secondary to age-related macular degeneration and to investigate the prognostic factors of visual outcomes. This study was a retrospective, observational case series that included 24 eyes of 24 patients who underwent PPV with subretinal tissue plasminogen activator and air for SMH. RPE tears were investigated using spectral-domain or swept-source optical coherence tomography images with raster scan, combined confocal scanning laser ophthalmoscope near-infrared images and color fundus photographs. Multiple regression analysis was performed to identify the predictors of visual outcome at month 3 and 6 after surgery. In 21 eyes out of 24 eyes (87.5%), RPE tear was detected in the posterior pole. Eight eyes (33.3%) had large RPE tears ( ≧ 1 disc diameter (DD)). Out of the 8 eyes, 5 eyes progressed fibrotic scars within 3 months despite successful SMH removal and showed decrease in their visual acuity (VA). The ratio of eyes with large RPE tears ( ≧ 1DD) were significantly higher in eyes which had undergone anti-VEGF therapy within 3 months than in treatment-naïve eyes (71.4% vs. 25.0%, p = 0.048). The multiple regression analysis revealed that a small RPE tear (< 1DD) and treatment-naïve condition were associated with better VA at month 3 and 6. SMH within 3 months after anti-VEGF therapy might be accompanied by a large RPE tear. An RPE tear which was smaller than 1DD and treatment-naïve condition were associated with better prognosis.